On Perturbations of Generators of C0-Semigroups. (1st December 2014) - Adler, Martin; Bombieri, Miriam; Engel, Klaus-Jochen
Abstract : We present a perturbation result for generators ofC 0 -semigroups which can be considered as an operator theoretic version of the Weiss-Staffans perturbation theorem for abstract linear systems. The results are illustrated by applications to the Desch-Schappacher and the Miyadera-Voigt perturbation theorems and to unbounded perturbations of the boundary conditions of a generator.